THE SIGNS OF THE NEW TEMPLE: THE ANALOGIES BETWEEN JESUS’ SIGNS AND THE TABERNACLE SIGNS IN JOHN'S GOSPEL - Lam, Tat Yu (My University, 2020)
In Johannine studies, the interpretation of σημεία is diverse. Traditionally, scholars tend to support that seven signs are chosen in John’s Gospel to structure Jesus’ public ministry (John 1:20—12:50). Some scholars, influenced by Bultmann’s hypothesis of a signs-source, scrutinize the underlying source, redaction, or traditions about the Johannine σημεία; others employ the literary narrative approach using either a Western or an ancient literary framework. Still others examine σημεία through a theological thematic lens chosen from John or the Old Testament. However, two fundamental questions remain unresolved: (1) Does John mean to include only seven signs to structure the public ministry when signs are claimed in the conclusion to be the theme of the Gospel (John 20:30-31)? (2) What among the many things Jesus does in the account qualify as signs for John? From a new perspective, this research points out that the Johannine σημεία, as specified in the text, refer to Jesus’ body as the new temple (his death and resurrection, John 2:18-22) and the provision of manna as the signs (John 6:30-35) forming the foundation for interpreting the use and selection of σημεῖα in John. This indicates a relationship between Jesus’ signs and the tabernacle signs which involve complex metaphors and associations including non-tabernacle signs in the OT in structuring the Gospel in its final form (John 20:30-31). Using a comparative method adapted from Hasan’s sociolinguistic theory of contextual configuration, I argue that Jesus’ signs represent the functions of the four tabernacle signs (a pot of manna, Aaron’s staff, the bronze altar cover, and the bronze serpent) along with other metaphors and associations in three phases (John 1-5; 6-12; 13-21) through which to reveal his grace and life-giving power and to authenticate his identity. Ultimately, through Jesus’ “all inclusive” σημεΐον in his Passion—the self-sacrificial crucifixion, resurrection, and appearances—his believers become the children of God and their faith is built not by seeing signs but by following Jesus’ words (i.e. loving one another and caring for other believers’ needs) to love him daily so that they have life in him.
Keywords: σημεία; Johannine; Tabernacle Signs; John’s Gospel